Hybridogenesis as an intermediate step between sexual reproduction and parthenogenesis in stick insects - Alexander Brandt; Guillaume Lavanchy; Vincent Mérel; Luca Soldini; Morgane Massy; Zoé Dumas; Emelyne Gaudichau; Marjorie Labedan; Falon Pasquier Genoud; Marc Bastardot; Tanja Schwander (Proceedings of the National Academy of Sciences, 2026)
Many organisms reproduce through noncanonical modes such as parthenogenesis or hybridogenesis (clonal transmission of one parent’s chromosomes), but whether these arise abruptly or stepwise from each other remains unclear. We address this in the stick-insect genus Bacillus , which harbors several hybrid lineages with diverse reproductive modes. From haplotype-resolved phylogenies of >500 wild-caught individuals, we infer a single, recent (~8,000 y) origin of all hybrids. The ancestral hybrid reproduced via hybridogenesis, which subsequently diversified into parthenogenesis and, twice independently, into triploid lineages. Laboratory crosses recapitulate this trajectory, where each step facilitated the next. These findings reveal how a single genomic perturbation can act as a catalyst for evolutionary innovation, turning the loss of sex into a driver of diversification rather than a dead end.